PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN ( Studi Pada Pelanggan Kantor Pos Semarang ) - Desinta Dwiyanti Putri, 13.05.51.0157 (Students' Journal of Economic and Management, 2017)
This study aims to determine the effect of quality consists of physical evidence, reliability, responsiveness, assurance, and empathy for customer satisfaction and analyze the most dominant factor influencing customer satisfaction.The population in this study are customers of Semarang Post Office Samples were taken by 100 respondents with non-probability sampling using purposive sampling are called judgmental sampling based on ratings (judgmental) research about people who deserve (eligible) to be sampled. The results showed that all independent variables Significant positive effect on customer satisfaction. From the analysis, explained that Overall, the independent variables proved to have a positive and significant impact on customer satisfaction. Keywords: Physical evidence, reliability, responsiveness, assurance, empathy, Customer Satisfaction